Detection of enzymatic compounds and antagonism of Bacillus species on the development of Macrophomina phaseolina (Bioagro, 2025)
Macrophomina phaseolina (Tassi) Goid is a pathogen that causes damping off, stem rot and root rot disease in a broad host range. The method of biological control using bacteria of the genus Bacillus stands out as viable and effective in combating plant diseases. The aim of the present study was detecting the presence of enzymatic compounds produced by the Bacillus isolates and evaluating the in vitro antagonistic activity of the bacterial isolates against M. phaseolina, using the methods of paired culture, pathogen culture on antagonist culture, thermostable and volatile metabolites. The experiments were carried out at the Phytopathology Laboratory, Department of Technology and Social Science, Campus III – UNEB, in Juazeiro-BA. Of the nine Bacillus isolates provided by the LBM, all were molecularly identified, except for isolate B7. The fungus M. phaseolina was acquired from the Dept. of Micologia at Federal University of Pernambuco. The experiment was in a completely randomized design for the enzymatic test using three replicates, and for the antagonism studies a 4x5 factorial arrangement was used (four isolates and four methods of antagonistic activity and the control treatment) with five replicates. Data were subjected to analysis of variance and Scott-Knott test at 5% probability. The enzymes showed the rates: proteases (100 %), cellulases (88%), pectinases (77 %), and amylases (66 %), suggesting that the isolates could be promising in the biological control of pathogens. In the selection of isolates with greater antagonistic activity, the method of culturing the pathogen on the culture, proved to be the most efficient in inhibiting the growth of M. phaseolina.
Keywords: Biological control; hydrolytic enzymes; soil fungi